2013
DOI: 10.1002/j.2161-0045.2013.00044.x
|View full text |Cite
|
Sign up to set email alerts
|

Academic Support Services and Career Decision‐Making Self‐Efficacy in Student Athletes

Abstract: This study examined the relationship between evaluations of academic support services and student athletes' career decision-making self-efficacy. One hundred and fifty-eight NCAA athletes (68% male) from 11 Division I teams completed measures of satisfaction with their academic support services, career decisionmaking self-efficacy, general self-efficacy, and locus of control. Results indicated that evaluations of academic support services were positively related to levels of career decision-making self-efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 17 publications
(26 reference statements)
0
51
1
2
Order By: Relevance
“…There is clear evidence linking self-efficacy theory to career development amongst college students (Burns, Jasinski, Dunn, & Fletcher, 2013;Fouad, Cotter, & Kantamneni, 2009;Scott & Ciani, 2008). A similar approach might also promote healthy psychosocial development.…”
Section: Ecological Map For the Athletic Well-being Modelmentioning
confidence: 99%
“…There is clear evidence linking self-efficacy theory to career development amongst college students (Burns, Jasinski, Dunn, & Fletcher, 2013;Fouad, Cotter, & Kantamneni, 2009;Scott & Ciani, 2008). A similar approach might also promote healthy psychosocial development.…”
Section: Ecological Map For the Athletic Well-being Modelmentioning
confidence: 99%
“…Research conducted by Cox et al (2004) also supports this notion, stating that obligations associated with being a college student-athlete can be detrimental to their career development. Thus, many colleges and university career centers offer an array of services and workshops, and have improved their service offerings in response to college student-athletes' time limitations as well as their understanding that college student-athletes are susceptible to lagging behind in their academic and career development progress (Burns, Jasinski, Dunn & Fletcher, 2013;Carodine et al, 2001). …”
Section: The Role Of Career Servicesmentioning
confidence: 99%
“…College student-athletes do not tend to engage themselves in establishing a defined career path outside of their participation in athletics (Martens & Lee, 1998), rendering them incapable of making effective and well thought out career decisions (Burns et al, 2013). Though only a few college student-athletes actually utilize their campus career centers, college and university career centers are an important resource for engaging college student-athletes in the career development process (Martens & Lee, 1998).…”
Section: The Role Of Career Servicesmentioning
confidence: 99%
“…An athletic department would benefit from controlling the course selection of its student-athletes to avoid NCAA eligibility issues. On the other hand, this lack of decision-making by student-athletes can negatively impact their academic development (Burns, Jasinski, Dunn, & Fletcher, 2013;Hardin & Pate, 2013;McPherson, 2013).…”
Section: Academic Challengesmentioning
confidence: 99%
“…This control exhibited by intercollegiate athletics has been shown to hinder the academic development of student-athletes (Burns et al, 2013;Hardin & Pate, 2013;McPherson, 2013 (Benson, 2000;Simons, Van Rheenen, & Covington, 1999). Huml et al found student-athletes were more confident their academic or faculty advisor would keep their academics a priority compared to their athletic advisor.…”
Section: Culture Of Intercollegiate Athleticsmentioning
confidence: 99%